Analisis Jaringan Kolaborasi Penelitian tentang Teknologi Blockchain dalam Keuangan dengan Pendekatan Bibliometrik - Judijanto, Loso; Sahusilawane, Wildoms; Utami, Eva Yuniarti (Eastasouth Institute, 2024)
This research applies bibliometric analysis to explore and identify research trends as well as research collaboration networks related to the application of blockchain technology in the financial sector. Leveraging major scientific research databases, such as PubMed, IEEE Xplore, and ScienceDirect, we collected 980 research articles published between 2014 and 2024. Through literature clustering analysis, we grouped articles into 11 clusters, covering aspects of blockchain adoption in banking, the advantages of blockchain technology in international trade, transparency issues, financial risks, and current topics such as auditing and supply chain finance. Research trend analysis illustrates the evolution of research topics over time, highlighting the increased focus on specific aspects in recent years. The most impactful articles and potential topics for future research provide direction for researchers and practitioners in this field. Analysis of author collaboration networks identifies close relationships between authors, creating collaboration opportunities that can increase the richness of multidisciplinary research in the future.